Interaksi Sosial Antar masyarakat Multikultur dalam Mengembangkan Solidaritas Sosial Masyarakat Kelurahan Gurabesi Kota Jayapura - Yowei, Amsal (JURNAL EKOLOGI BIROKRASI, 2022)
The purpose of this study is to analyze the social interaction of multicultural communities in increasing social solidarity in the neighborhood of RT 1,2,3 RW 7 Gurabesi Village, Jayapura City. Analyzing dominant aspects that can increase Social Solidarity and Analyzing a forum for assimilation that can accelerate the process of community Social Solidarity. Research on Social Interaction Between Multicultural Communities in Developing Social Solidarity (Case Study in RT 1,2,3 RW 7 Kelurahan Gurabesi Jayapura City) uses qualitative methods and uses case studies to describe and analyze social interactions between multicultural communities in RT 1,2,3 RW 7 Gurabesi Village. The reason for using qualitative methods is because this research goes through the process of observing and understanding community interactions in RT 1,2,3 RW 7 and can analyze and describe social interactions in communities in RT 1,2,3, RW 7, one of the characteristics of qualitative research. namely: carried out directly in natural conditions directly to the source of data and researchers involved key instruments and data collected in the form of words or pictures, research results. (1) Inter-community cooperation can be seen from various sectors of life, namely activities such as in the field of paving alleys and cleaning the Anafre River in RT 1,2,3 RW 7, which can be seen interacting between communities in the environment without distinguishing their religion and ethnicity. (2) The community always works together in every development within RT 1,2,3 RW 7 Gurabesi Village, Jayapura City, (3) Deliberations and Contributions with residents in RT 1,2,3 RW 7 Gurabesi Village. Implementation of the alms tradition Involved in the Recitation Event A series of Village/Rukun Alms events